Compressive strength of vege-grout bricks - Dzulkifli N.A.; Omar R.C.; Usman F.; Taha H.; Sanusi K.A. (Science Publishing Corporation Inc, 2023)
Brick is one of largest material used in construction of infrastructure all over the world. A conventional bricks such as clay brick and concrete brick are produced from clay with high temperature kiln firing and from ordinary Portland cement (OPC) concrete respectively. Both of this activities lead to CO 2 emission. The burning process requires high temperature at the same time release carbon dioxide and pollute the environment. At present, carbon emissions has become a crucial issues in the society that must be solved. Several studies had demonstrated that brick can be produced from bacteria based on Microbial Induced Calcite Precipitation (MICP). The objective of this study is to develop cement free- brick from vegetables waste with added eggshell as calcium additive to induce biocementation of brick. Brick specimen was cast in the mould size 210 90 65 mm and casting for 28 days. The study showed that there was an increased in compressive strength up to 0.062 N/mm 2 as the curing period increased to 28 days which showed the occurrence of biocementation activities. SEM-EDX analysis confirmed the presence of calcite precipitation. The result indicated that vege-grout can be used as binding agent for biocementation to produce bricks. 2018 Authors.